Cotinine versus questionnaire: early-life environmental tobacco smoke exposure and incident asthma - Carlsten Chris; Dimich-Ward Helen; DyBuncio Anne; Becker Allan B; Chan-Yeung Moira (BMC, 2012)
Abstract Background The use of biomarkers has expanded considerably, as an alternative to questionnaire-based metrics of environmental tobacco smoke (ETS); few studies have assessed the affect of such alternative metrics on diverse respiratory outcomes in children, and we aimed to do so. Methods We evaluated various measures of birth-year ETS, in association with multiple respiratory endpoints early years of life, in the novel context of a birth cohort at high risk for asthma. We administered questionnaires to parents, both at the end of pregnancy and at one year of life, and measured cotinine in cord blood (CCot; in 275 children) and in urine (UCot; obtained at 12 months in 365 children), each by radioimmunoassay. Multiple logistic regression was used to assess the association of the various metrics with recurrent wheeze at age 2 and with bronchial hyperresponsiveness (BHR) and asthma at age 7. Results Self-reported 3rd trimester maternal smoking was associated with significantly increased risk for recurrent wheeze at age 2 (odds ratio 3.5 [95% confidence interval = 1.2,10.7]); the risks associated with CCot and 3rd trimester smoking in any family member were similar (OR 2.9 [1.2,7.0] and 2.6 [1.0,6.5], respectively). No metric of maternal smoking at 12 months appeared to significantly influence the risk of recurrent wheeze at age 2, and no metric of ETS at any time appeared to significantly influence risk of asthma or BHR at age 7. Conclusions Biomarker- and questionnaire-based assessment of ETS in early life lead to similar estimates of ETS-associated risk of recurrent wheeze and asthma.